A Design for a Data and Information Service to Address the Knowledge Needs of the Water-Energy-Food (W-E-F) Nexus and Strategies to Facilitate Its Implementation - Lawford, Richard G. (Frontiers in Environmental Science, 2019)
Food security is essential to sustain human societies. Food production flourishes when water, energy, and land are abundant, but more often it is limited by scarcities in one or more of these resources. In particular, food production is limited by the relatively fixed amount of water that circulates in the hydrosphere, the lack of new land for crops in many countries, and the depletion of critical minerals and fossil fuels in many source regions. An integrated Water-Energy-Food (W-E-F) Nexus planning and management approach promises improved resource efficiencies, new business opportunities, more coherent resource and environmental policies, and economies of scale for the data and information services underpinning better decision-making. This paper distills discussions on data and information from four regional workshops held as part of a Future Earth W-E-F Nexus Cluster project. The workshops reviewed ways to enhance the sustainability of the W-E-F Nexus through better governance; collecting, analyzing, and communicating data and information; and integrating both with management for better planning and decision-making. The focus of this paper is to explore the potential application of an integrated data and information system to enhance water, energy, and food sustainability. In particular, this paper's objective is to explore how a multisector W-E-F Nexus data and information system could be developed and operated to meet the planning and decision-making information needs of practitioners and to facilitate the implementation of the W-E-F Nexus concept. This “Hypothesis and Theory” paper provides a hypothesis and system design and proposes steps that could be taken to implement and test the system in a W-E-F Nexus environment. Data and information, along with modern technologies, can play a central role in facilitating paradigm shifts that reinforce the W-E-F Nexus by explicitly assessing environmental services, meeting the growing urban food demand, valuing water and other resources used to produce food and energy for export, promoting resource use efficiency through integrated planning and management, and strengthening links between the W-E-F Nexus and appropriate Sustainable Development Goals.